Tularemia: A Rare Cause of Neck Mass - Karlidag, Turgut; Keles, Erol; Kaygusuz, Irfan; Yuksel, Koray; Yalcin, Sinasi (Galenos Yayincilik, 2015)
Objective: Tularemia is a bacterial zoonosis caused by Francisella tularensis. In this study, we aimed to retrospectively evaluate the documents of patients who had a diagnosis of tularemia in our hospital and discuss this condition with a literature review. Methods: Twenty-five patients who had a diagnosis of tularemia between 2010 and 2013 were included in the study. The patients were assessed with respect to their demographic data; presenting complaints; leukocyte, sedimentation, and C-reactive protein (CRP) values; applied treatment protocols; duration of stay in the hospital; and histopathological examinations. Results: Fifty-seven patients were admitted to the health department of our clinic with a preliminary diagnosis of tularemia, and the diagnosis of tularemia was serologically confirmed for 25 patients. Pharyngeal mucosa cultures, centrifuged serum samples, and abscess and/or pathological samples were collected from all the patients. Thirteen patients were female, and 12 were male. The ages of the patients were between 10 and 75 (average 33.12 +/- 15.53) years. The most frequent (100%) symptom among the patients was swelling in the neck. While abscess drainage was performed in 12 patients (48%), the neck mass was excised in 3 patients (12%), and 10 patients (40%) were given only medical treatment. According to the guide of tularemia management by the ministry of health, treatment using suitable doses of streptomycin was started for all the patients; in addition, for 8 (32%) patients, doxycycline treatment was added. Conclusion: In recent years, tularemia in our country has been increasing at some specific locations, and those patients are frequently admitted to polyclinics with a complaint of swelling in the neck. In endemic areas in particular, tularemia should also be considered in the differential diagnosis of patients who present with abscess in the neck.
Keywords: Tularemia; Francisella tularensis; neck abscess